Viral protein R (Vpr)-induced neuroinflammation and its potential contribution to neuronal dysfunction: a scoping review - Monray Edward Williams; Aurelia A. Williams; Petrus J.W. Naudé (BMC Infectious Diseases, 2023)
Abstract HIV-associated neurocognitive disorders (HAND) are the result of the activity of HIV-1 within the central nervous system (CNS). While the introduction of antiretroviral therapy (ART) has significantly reduced the occurrence of severe cases of HAND, milder cases still persist. The persistence of HAND in the modern ART era has been linked to a chronic dysregulated inflammatory profile. There is increasing evidence suggesting a potential role of Viral protein R (Vpr) in dysregulating the neuroinflammatory processes in people living with HIV (PLHIV), which may contribute to the development of HAND. Since the role of Vpr in neuroinflammatory mechanisms has not been clearly defined, we conducted a scoping review of fundamental research studies on this topic. The review aimed to assess the size and scope of available research literature on this topic and provide commentary on whether Vpr contributes to neuroinflammation, as highlighted in fundamental studies. Based on the specified selection criteria, 10 studies (6 of which were cell culture-based and 4 that included both animal and cell culture experiments) were eligible for inclusion. The main findings were that (1) Vpr can increase neuroinflammatory markers, with studies consistently reporting higher levels of TNF-α and IL-8, (2) Vpr induces (neuro)inflammation via specific pathways, including the PI3K/AKT, p38-MAPk, JNK-SAPK and Sur1-Trpm4 channels in astrocytes and the p38 and JNK-SAPK in myeloid cells, and (3) Vpr-specific protein amino acid signatures (73R, 77R and 80A) may play an important role in exacerbating neuroinflammation and the neuropathophysiology of HAND. Therefore, Vpr should be investigated for its potential contribution to neuroinflammation in the development of HAND.